Coagulation tests at trigger day in patients with Factor V Leiden Mutation to predict implantation failure - Devranoglu, Belgin; Yayla Abide, Cigdem; Ozkaya, Enis; Senol, Taylan; Kutlu, Tayfun; Kayatas Eser, Semra (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objectives: The aim of this study was to assess the predictive value of coagulation tests at trigger day in patients with isolated factor V Leiden mutation who underwent intracytoplasmic sperm injection cycle (ICSI). Study Design: Ninety women with isolated factor V Leiden mutation underwent ICSI cycles with an indication of unexplained infertility. In all participants antagonist protocol was used for ovarian hyperstimulation and coagulation tests including activated partial thromboplastin time (APTT), partial thromboplastin time (PT), international normalized ratio (INR), serum fibrinogen and D-dimer levels at trigger day were determined to predict successful implantation. All the clinical parameters specific for the treatment and some patient characteristics were recorded for each participants. Results: There was no significant difference between groups with and without succesfull implantation in terms of age, body mass index, basal hormone levels (follicle stimulating hormone, estradiol, progesterone at day 3 and antimullerian hormone) (P > 0.05). Estradiol and progestrone levels at trigger day were comparable between groups (P > 0.05). Groups had similar endometrial thickness at embryo transfer day (P > 0.05). Some ovarian stimulation characteristics including initial gonadotropin dose, number of follicles > 17 mm, number of oocytes harvested and number of embryos were similar between groups (P > 0.05). Although there was no significant difference between groups with regard to APTT and PT levels, INR level were significantly lower while D-dimer levels and fibrinogen were significantly higher in cases without implantation (P < 0.05). Conclusion: D-dimer, fibrinogen and INR levels were significant predictors for successful implantation in women with isolated factor V Leiden who underwent ovulation hyperstimulation.